IL-1β and TNFα Differentially Influence NF-κB Activity and FasL-Induced Apoptosis in Primary Murine Hepatocytes During LPS-Induced Inflammation - Rex, Julia; Lutz, Anna; Faletti, Laura E.; Albrecht, Ute; Thomas, Maria; Bode, Johannes G.; Borner, Christoph; Sawodny, Oliver; Merfort, Irmgard (Frontiers in Physiology, 2019)
Macrophage-derived cytokines largely influence the behavior of hepatocytes during an inflammatory response. We previously reported that both TNFα and IL-1β, which are released by macrophages upon LPS stimulation, affect Fas ligand (FasL)-induced apoptotic signaling. Whereas TNFα preincubation leads to elevated levels of caspase 3 activity and cell death, pretreatment with IL-1β induces increased caspase-3 activity but keeps cells alive. We now report that IL-1β and TNFα differentially influence NF-κB activity resulting in a differential upregulation of target genes, which may contribute to the distinct effects on cell viability. A reduced NF-κB activation model was established to further investigate the molecular mechanisms which determine the distinct cell fate decisions after IL-1β and TNFα stimulation. To study this aspect in a more physiological setting, we used supernatants from LPS-stimulated bone marrow-derived macrophages (BMDMs). The treatment of hepatocytes with the BMDM supernatant, which contains both IL-1β and TNFα, sensitized to FasL-induced caspase-3 activation and cell death. However, when TNFα action was blocked by neutralizing antibodies, cell viability after stimulation with the BMDM supernatant and FasL increased as compared to single FasL stimulation indicating the important role of TNFα in the sensitization of apoptosis in hepatocytes. These results give first insights into the complex interplay between macrophages and hepatocytes which may influence life/death decisions of hepatocytes during an inflammatory reaction of the liver in response to a bacterial infection.